Progress Monitoring Measures in Psychotherapy and Mental Health: Examination of a Structural Equation Model: English - Bourque, Caissie; Charbonneau, Andréanne; Bouchard, Geneviève; Lachance-Grzela, Mylène (Canadian Journal of Counselling and Psychotherapy, 2022)
Progress monitoring measures are psychometric assessments designed to monitor treatment progress by evaluating global ratings of mental health. Their use in clinical practice is related to increases in the effectiveness of therapy and decreases in negative outcomes. Yet, clinicians often report struggling with limited understanding of the differences between the numerous measures available, and only a small percentage of clinicians report using them. In order to assist clinicians in measure selection, the current study documented and compared the ability of five measures (i.e., the ORS, the OQ-45, the BASIS-24, the CORE-OM, and the TOP) to assess two aspects of mental health: psychological well-being and psychological distress. Data from a clinical sample of 53 French-speaking individuals were analyzed using structural equation modelling. Results showed strong convergent validity between the measures and indicated that they evaluated mental health accurately. Further analysis specified that, among the five measures, the OQ-45 and the CORE-OM were the best at assessing mental health.